Phenotype variation of hypertrophic cardiomyopathy in carriers of the p.Arg870His pathogenic variant in the MYH7 gene - A. N. Kucher; N. R. Valiakhmetov; R. R. Salakhov; M. V. Golubenko; E. N. Pavlyukova; M. S. Nazarenko (Бюллетень сибирской медицины, 2022)
The review analyzes variability of clinical manifestations of p.Arg870His in the MYH7 gene, which is repeatedly registered in patients with hypertrophic cardiomyopathy (HCM). The analysis involves the data from scientific publications obtained as a search result in the PubMed, СlinVar, and eLibrary.ru databases, as well as authors’ own results. A wide range of phenotypic manifestations have been revealed in carriers of p.Arg870His, from the asymptomatic to severe course, rapid progression, and early death. The review considers possible factors that modify the effect of the pathogenic variant (i.e. dosage of the pathogenic variant, the presence of other unfavorable genetic variants, etc.). The importance of accumulating information on the clinical features of HCM in the carriers of specific gene variants is emphasized in order to clarify their pathogenicity and to identify factors modifying the clinical outcome, which is important for the choice of the treatment strategy for HCM.